STRUKTUR DAN DISTRIBUSI PENDAPATAN RUMAH TANGGA PETANI KELAPA SAWIT POLA SWADAYA DESA KOTA TENGAH KECAMATAN DOLOK MASIHUL KABUPATEN SERDANG BEDAGAI SUMATERA UTARA - Gurning, Elista K.; Edwina, Susy; ', Yusmini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study was (1) to analyze the structure of household income independent smallholder farmers of oil palm at Kota Tengah Village Dolok Masihul District Of Serdang Bedagai Regency North Sumatera, (2) to analyze the distribution of household income independent smallholder farmers of oil palm at Kota Tengah Village Dolok Masihul District Of Serdang Bedagai Regency North Sumatera. The method used in this study is a survey method and number of samples were determinated by purposive sampling method. The population in this study was 102 farmers and is sampled 20 farmers. The result of research showed that the agricultural sector is the largest contributor to the total household income of oil palm farmers is equal to 54,93% and from non-agricultural sectors of 45,07%. Revenues from the agricultural sector dominated from oil palm farming 46,07% and cassavas farming 8,86%. The distribution of household income independent smallholder farmers of oil palm at Kota Tengah Village Dolok Masihul District Of Serdang Bedagai Regency North Sumatera is at a low ineguality with index gini ratio 0,18. It means that the distibution of household income among the oil palm farmers is relative evenly. Keywords: Income Structure, Income Distribution, Index Gini Ratio